Rancang Bangun Sistem Irigasi pada Perkebunan Cabai Berbasis Arduino Uno dan Sprinkler - Rahman, Arraafi; Simanjuntak, Imelda Uli Vistalina (Majalah Ilmiah Teknologi Elektro, 2022)
Red chili is one type of vegetable widely used by the people of Indonesia because it has a reasonably high selling value. One of the causes of soaring chili prices is when there is much demand, but the farmers' harvest is insufficient. This incident often occurs because harvests often fail due to the manual and uneven irrigation system. So chili farmers in highland areas that rarely rain must be assisted by a regular and automatic irrigation system. Therefore, this study aims to help chili farmers to water the red chili plants as needed with the help of a water pump. The designed water pump system supports a DC of 12 volts and a power of 18 watts. The strategy used for watering chilies is a bulk water system, which emits water to the plants so that watering distributes at all points of the red chili. Transmission water velocity is measured using a water flow sensor. Likewise with the soil moisture parameters using sensors which state that the soil conditions are PH > 2.0 (wet) and PH > 5.51- 7.00 (very humid). After the soil, the moisture value is read by Arduino Uno Atmega 2560, and the results will display on the LCD. Watering will adjust to the water needs based on the PH value obtained.